Entering the Digital Therapy Room: Best Practices for Telepractice Interventions With School-Age Clients. Issue 2 (April 2022) - Bolden, William; Grogan-Johnson, Sue
Abstract : School-based speech–language pathologists (SLPs) have been plunged into telepractice service delivery with the ongoing COVID-19 pandemic. However, this temporary shift to provide online instruction is not the same as fully implementing a telepractice service delivery model that is comparable with in-person service delivery. The purpose of this article is to provide the practicing SLP with a framework for delivering effective intervention services to school-age students with language impairments via telepractice. Within this framework, the SLP still must consider the available evidence base for an intervention and implement its core components, including repeated opportunities for skill and knowledge acquisition with sufficient intensity, systematic scaffolding, and an explicit focus (Ukrainetz, 2006a ). Particular attention must be given to aspects of intervention planning, manipulation of the therapy context, collaboration with relevant stakeholders, specific intervention materials, and prompting because these are among the most likely to differ between the telepractice and in-person service delivery. We discuss these aspects and provide examples.